What Industries Move the NT Ratio? Exploring the Linkage between the NT Ratio and Industry Returns in Japan - Tsuji, Chikashi (Archives of Business Research, 2014)
This paper investigates which industries drive the recent high NT ratio in Japan. Our empirical examinations derive the following evidence. First, (1) for our first half sub-sample period before the US Lehman shock, it is only the return of transportation industry that is relatively strongly connected with the changes of the NT ratio. Second, we also find that (2) for our latter half sub-sample period, the industries which are relatively strongly connected with the recent higher NT ratio are foods, textiles and apparel, chemicals, pharmaceuticals, glass and ceramics, electric machinery, precision instruments, other manufacturing, retail, communications, and warehousing industries. This evidence after the US Lehman shock also suggests that the linkage between the NT ratio and the above eleven industry returns becomes stronger. On the other hand, we further clarify that (3) the returns of electric power industry always show the statistically significant negative correlations with the changes of the NT ratio regardless of the sample periods. Keywords: Industry stock returns; Nikkei 225; NT ratio; TOPIX.